Design and In Vitro Evaluation of Transfersomal Gel System: A Novel Approach for Transdermal Drug Delivery - Mishra, Namrata; Tripathi, Avanish (Journal of Neonatal Surgery, 2025)
The present research involves the formulation, optimization, and evaluation of a transfersomal gel (NTFG7) aimed at enhancing the dermal delivery of drugs. Transferosomes were formulated and incorporated into a gel base containing Carbopol 934 (0.25%), propylene glycol (0.5%), ethanol (0.5%), and methyl paraben (0.02%). The gel was optimized by adjusting the concentration of Carbopol 934 to obtain desirable consistency and drug release properties. The optimized formulation (NTFG7) was subjected to various physicochemical evaluations, including visual appearance, homogeneity, pH, viscosity, swelling index, and in vitro drug release studies. The gel was found to be smooth, off-white, odorless, and homogeneous with a pH of 7.7 ± 0.05 and viscosity of 11,279 ± 0.63 cps. The swelling index was recorded as 65.11 ± 0.02%, indicating excellent hydration potential. In vitro drug release studies showed a sustained release profile, with 96.54% cumulative release over 12 hours. Kinetic modeling of the release data revealed that the drug followed Korsmeyer–Peppas kinetics (R² = 0.995), suggesting an anomalous non-Fickian diffusion mechanism. Stability studies conducted over three months at varying temperatures (4°C, 25°C, and 40°C) showed no significant changes in physical appearance, pH, or viscosity, confirming the formulation’s stability. These results suggest that the optimized transfersomal gel formulation (NTFG7) is a promising carrier for controlled and efficient transdermal drug delivery.